Microstructure, Hardness and EIS Evaluation of Ti-15Zr-5Nb Dental Alloy - Hulka, Iosif; Mirza-Rosca, Julia Claudia; Saceleanu, Adriana; Uțu, Ion-Dragoș (MDPI AG, 2024)
Ti alloys have been widely used in biomedical applications due to their special properties. They have specific properties such as biocompatibility, biofunctionality and high corrosion resistance, which enable them to function inside the human body. Among them, Ti-6Al-4V is probably one of the most widely used alloys for implants. However, aluminum and vanadium ions have been reported to cause problems and adverse reactions in the human body over long periods. Thus, in the present study, Ti–15Zr–10Nb alloy synthesized by high vacuum melting was manufactured and characterized by different techniques. The phase composition was determined by XRD. This showed the presence of α and β phases in the alloy, consistent with the microstructural study. From a microstructural point of view, the alloy shows lamellar and acicular structures with α-grain boundaries. Vickers microhardness measurements showed an increased hardness compared to Ti-CP. Furthermore, the electrochemical behavior was evaluated using HCl as an electrolyte. The obtained results were compared to Ti-CP tested in the same electrochemical condition. The studies indicated that Ti-CP presents a nobler electrochemical behavior than Ti-15Zr-5Nb. Thus, despite the very good corrosion properties of Ti-15Zr-5Nb in a simulated oral environment and Ringer’s solutions, the present study reveals that the Ti-15Zr-5Nb alloy has lower corrosion resistance in aggressive media when compared to Ti-CP.
Keywords: biomaterials; Ti–15Zr–10Nb; microstructure; hardness; EIS